Enfoque ciência-tecnologia-sociedade nos seminários integrados: potencialidades e desafios identificados para o ensino de física - Silva, Josiane Marques da (2016)
In 2012 the secondary education the state of Rio Grande do Sul underwent a curricular reorganization called as Polytechnic Education. This new proposal for Secondary Education directs that the school curriculum is organized by area of knowledge, the content approach are buoyed by guiding principles, that the evaluation is emancipatory, understands the work as an educational principle, and provides for inclusion of joint spaces of knowledge called Integrated Seminars. In view of these guidelines it is understood that the pedagogical practice is changing, thus, the present study aims to investigate the contributions of a didactic proposal buoyed the assumptions Science-Technology-Society to develop classes in Integrated Seminars of space according to the purposes thereof. This study is qualitative and as instruments for data collection form used questionnaires, logbook and reviews of student written productions. The data analysis was guided by the Discursive Textual Analysis, from four analytical categories: (I) Conceptions on the Implementation of the Polytechnic Education; (II) Development of Integrated Seminars; (III) Teacher Formation; (IV) Approximations of assumptions STS with the Purposes of the Integrated Seminars. Signals the need for discussions on the Polytechnic Education, in particular on issues related to the collective work of teachers for planning teaching practices in accordance with the purposes of the proposed curriculum in an interdisciplinary and contextualized perspective, we realize the need that the workload of teachers should be rethought in order to organize teacher training spaces to address the assumptions of the Polytechnic Education and perspectives and methodologies that can be bench marks of educational work in line with the objectives of the proposed curriculum. It is noteworthy that the assumptions of the Science-Technology-Society approach are configured as a possibility to support the preparation and development of classes in the context of Integrated Seminars of the Natural Sciences area, covering interdisciplinarity, contextualization and socially relevant themes approach. Finally, it signals the need of joint partnerships between university, school and state education department for conducting teacher training spaces for those found clashes are overcome.